UNDERSTANDING THE EPIDEMIOLOGICAL ASPECTS OF DENGUE IN THE LAST 5 YEARS IN ANÁPOLIS (CIPEEX, 2026)
Introduction: Dengue is an arbovirus transmitted by Aedes aegypti and one of the greatest public health challenges in Brazil. The Central-West region has a high incidence, particularly in Anápolis, Goiás, which accounts for a significant percentage of the state's cases. Understanding its epidemiological profile is essential for prevention and effective public policies. Methodology: This was an ecological observational study using dengue data reported in Anápolis between 2019 and 2024, obtained from SINAN. All cases were included, except duplicate or incomplete records. An integrative review of national and international databases (2020–2025) was also conducted to discuss the results. The data were tabulated and statistically analyzed. Results: Between 2020 and 2024, Goiás confirmed 216,385 cases, of which 94,415 (43.6%) were in Anápolis. The peak occurred in 2024 (45,422 cases) and the lowest number was in 2021 (4,075). Adults aged 20 to 44 were the most affected (45.2%), with a female predominance (54.8%). Fever, headache, and myalgia were the most common symptoms, while vomiting and retro-orbital pain were less frequent and associated with severe forms. Neighborhoods such as Jaiara and Jardim Alexandrina concentrated the highest number of cases. These data corroborate the literature. Conclusion: Anápolis accounted for more than 40% of dengue cases in the state, primarily affecting the economically active population. The results reinforce the need for continued surveillance, standardized reporting, and targeted interventions for the most vulnerable areas and groups.
Keywords: Dengue; arbovirus; Epidemiology